Moves that Matter: Issue Selling and Organizational Change - Dutton, Jane E.; Ashford, Susan J.; O’Neill, Regina M.; Lawrence, Katherine (Academy of Management Journal, 2001)
In this study, we examined 82 accounts of ?issue selling? to better understand managers' implicit theories for successfully shaping change from below by directing the attention of top management. The study reveals the importance of various issue-selling moves, including packaging, involvement, and timing. Managerial accounts uncover three kinds of contextual knowledge that are critical to the execution of issue-selling moves. The study shows managers actively shaping the issue-selling microprocesses that contribute to organizational change.